2021
DOI: 10.3177/jnsv.67.180
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Profile in 18 Patients with Rheumatic Diseases Treated with Glucocorticoids and BCAAs

Abstract: The administration of glucocorticoids to patients with rheumatic diseases often results in glucocorticoid-induced myopathy. We previously found that administration of branched-chain amino acids (BCAA) to such patients improves the loss of skeletal muscle, however, their individual differences were often observed. The present study, therefore, aims to identify specific parameters associated with BCAA-induced increases in skeletal muscle mass. Eighteen patients with rheumatic diseases treated with prednisolone w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It was reported that the supplementation of BCAAs may reduce the muscle damage for patients with rheumatic diseases. It was demonstrated that plasma BCAAs, aspartic acid, and glutamate concentrations correlate positively with the rate of improvement in biceps femoris muscle atrophy, suggesting that these amino acids are associated with the BCAA-induced increase in muscle mass [24]. It was also demonstrated that, for patients treated in intensive care units, the supplementation of L-amino acids can protect skeletal muscle mass and function; for severely ill patients, a higher provision of protein and L-amino acids has been associated with a lower mortality [25].…”
Section: Muscle Statusmentioning
confidence: 99%
“…It was reported that the supplementation of BCAAs may reduce the muscle damage for patients with rheumatic diseases. It was demonstrated that plasma BCAAs, aspartic acid, and glutamate concentrations correlate positively with the rate of improvement in biceps femoris muscle atrophy, suggesting that these amino acids are associated with the BCAA-induced increase in muscle mass [24]. It was also demonstrated that, for patients treated in intensive care units, the supplementation of L-amino acids can protect skeletal muscle mass and function; for severely ill patients, a higher provision of protein and L-amino acids has been associated with a lower mortality [25].…”
Section: Muscle Statusmentioning
confidence: 99%